Victims’ perspectives towards sexual harassment prevention measures at work: Victims’ voices to build an anti-harassment working environment - Nguyen, Hong Thu Thi; Le, Giang Thi (Intersections. East European Journal of Society and Politics, 2024)
This mixed-method study revolves around female victims’ perspectives and voices concerning sexual harassment prevention measures in their workplaces. Two hundred and eighty-nine participants responded to questionnaires, in-depth questions, and interviews (with 20 interviewees). Data were collected from various professionals who had experienced sexual misconduct at work. The research objectives were to investigate victims’ perspectives of sexual harassment prevention and the effectiveness of related measures, to examine the impact of sexual harassment measures on work-related motivation, and to explore female employees’ voices concerning reforms involving the implementation of sexual harassment prevention measures. The quantitative results reveal that the victims did not highly evaluate the effectiveness of sexual harassment prevention measures implemented at their workplaces. Also, the measures negatively impacted employees’ work-related motivation. Qualitative data indicated that the victims strongly recommended positive changes in sexual harassment awareness education, sexual harassment laws, and women’s protection policies to create an anti-sexual harassment working environment.